2007
DOI: 10.1016/j.apm.2006.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Steady state analysis of an Mx/G/1 queue with two phase service and Bernoulli vacation schedule under multiple vacation policy

Abstract: This paper examines the steady state behaviour of a batch arrival queue with two phases of heterogeneous service along and Bernoulli schedule vacation under multiple vacation policy, where after two successive phases service or first vacation the server may go for further vacations until it finds a new batch of customer in the system. We carry out an extensive stationary analysis of the system, including existence of stationary regime, queue size distribution of idle period process, embedded Markov chain stead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 24 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…In recent years, extensive amount of work has been done on batch arrival queues with vacations and breakdowns. We mention a few recent papers by Kumar and Arumuganathan [16], Choudhury, Tadj and Paul [17], Maraghi, Madan and Darby-Dowman [18], Khalaf, Madan and Lukas [19].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive amount of work has been done on batch arrival queues with vacations and breakdowns. We mention a few recent papers by Kumar and Arumuganathan [16], Choudhury, Tadj and Paul [17], Maraghi, Madan and Darby-Dowman [18], Khalaf, Madan and Lukas [19].…”
Section: Introductionmentioning
confidence: 99%
“…This overhauling can be utilized as a vacation in the presented model. Another application of such model based on Choudhury et al [17] may well be found in some transportation systems in which a ferry driver or locomotive driver may have a vacation after every round of trip.…”
Section: Introductionmentioning
confidence: 98%
“…A numbers of papers [13][14][15][16] have recently appeared in queueing literature in which the server provides to each heterogeneous service with Bernoulli schedule vacation (BSV). The so-called BSV means that when the service of a unit is completed, the server may leave for a vacation of random length with probability p or may continue to serve the next unit, if any with probability 1 À p (see Choudhury et al [17]). For the multiple server vacation models, there are only a limited number of studies due 0307-904X/$ -see front matter Ó 2010 Elsevier Inc. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, the server waits for the first customer to arrive. Recently, there has been considerable attention paid to the study of M/G/1-type queuing systems with two phases of service under Bernoulli vacation schedule and different vacation policies, see Choudhury et al (2007), and Madan (2005, 2004), in which after two successive phases of service, the server may go for Bernoulli vacation. Further, Haridass and Arumuganathan (2011) investigated a bulk service queueing system with variant threshold policy for secondary jobs, which is related to our two phase queueing system.…”
Section: Introductionmentioning
confidence: 99%